L-isoleucine-supplemented Oral Rehydration Solution in the Treatment of Acute Diarrhoea in Children: A Randomized Controlled Trial (Journal of Health, Population and Nutrition, 2011)
Antimicrobial peptides represent an important component of the innate immune defenses of living organisms, including humans. They are broad-spectrum surface-acting agents secreted by the epithelial cells of the body in response to infection. Recently, L-isoleucine and its analogues have been found to induce antimicrobial peptides. The objectives of the study were to examine if addition of L-isoleucine to oral rehydration salts (ORS) solution would reduce stool output and/or duration of acute diarrhoea in children and induce antimicrobial peptides in intestine. This double-blind randomized controlled trial was conducted at the Dhaka Hospital of ICDDR,B. Fifty male children, aged 6-36 months, with acute diarrhoea and some dehydration, attending the hospital, were included in the study. Twenty-five children received L-isoleucine (2 g/L)-added ORS (study), and 25 received ORS without L-isoleucine (control). Stool weight, ORS intake, and duration of diarrhoea were the primary outcomes. There was a trend in reduction in mean±standard deviation (SD) daily stool output (g) of children in the L-isoleucine group from day 2 but it was significant on day 3 (388±261 vs 653±446; the difference between mean [95% confidence interval (CI) (-)265 (-509, -20); p=0.035]. Although the cumulative stool output from day 1 to day 3 reduced by 26% in the isoleucine group, it was not significant. Also, there was a trend in reduction in the mean±SD intake of ORS solution (mL) in the L-isoleucine group but it was significant only on day 1 (410±169 vs 564±301), the difference between mean (95% CI) (-)154 (-288, -18); p=0.04. The duration (hours) of diarrhoea was similar in both the groups. A gradual increase in stool concentrations of ß-defensin 2 and 3 was noted but they were not significantly different between the groups. L-isoleucine-supplemented ORS might be beneficial in reducing stool output and ORS intake in children with acute watery diarrhoea. A further study is warranted to substantiate the therapeutic effect of L-isoleucine. Key words: Dehydration; Diarrhoea, Acute; Diarrhoea, Infantile; Double-blind method; Oral rehydration solutions; Randomized controlled trials; Bangladesh DOI: http://dx.doi.org/10.3329/jhpn.v29i3.7864 J HEALTH POPUL NUTR 2011 Jun;29(3):183-190